An emerging maestro of immune regulation: how DOT1L orchestrates the harmonies of the immune system - Kealy, Liam; Runting, Jessica; Thiele, Daniel; Scheer, Sebastian (Frontiers in Immunology, 2024)
The immune system comprises a complex yet tightly regulated network of cells and molecules that play a critical role in protecting the body from infection and disease. The activity and development of each immune cell is regulated in a myriad of ways including through the cytokine milieu, the availability of key receptors, via tailored intracellular signalling cascades, dedicated transcription factors and even by directly modulating gene accessibility and expression; the latter is more commonly known as epigenetic regulation. In recent years, epigenetic regulators have begun to emerge as key players involved in modulating the immune system. Among these, the lysine methyltransferase DOT1L has gained significant attention for its involvement in orchestrating immune cell formation and function.In this review we provide an overview of the role of DOT1L across the immune system and the implications of this role on health and disease. We begin by elucidating the general mechanisms of DOT1L-mediated histone methylation and its impact on gene expression within immune cells. Subsequently, we provide a detailed and comprehensive overview of recent studies that identify DOT1L as a crucial regulator of immune cell development, differentiation, and activation. Next, we discuss the potential mechanisms of DOT1L-mediated regulation of immune cell function and shed light on how DOT1L might be contributing to immune cell homeostasis and dysfunction. We then provide food for thought by highlighting some of the current obstacles and technical limitations precluding a more in-depth elucidation of DOT1L's role. Finally, we explore the potential therapeutic implications of targeting DOT1L in the context of immune-related diseases and discuss ongoing research efforts to this end.Overall, this review consolidates the current paradigm regarding DOT1L's role across the immune system and emphasises its critical role in governing the healthy immune system and its potential as a novel therapeutic target for immune-related diseases. A deeper understanding of DOT1L's immunomodulatory functions could pave the way for innovative therapeutic approaches which fine-tune the immune response to enhance or restore human health.